Technical Study of Sediment Pond Maintenance Scheduling ( Sediment pond) For Guard Quality Sand Wash PT. Gunung Source Fortune - Fitra Alif Sairozi; Lakon Utamakno; Yudho Dwi Galih Cahyono (Journal of Applied Sciences, Management and Engineering Technology, 2022)
PT. Gunung Sumber Rejeki is a subsidiary of PT. Agung Satrya Abadi which is located at Wonosunyo Village, Kec. Gempol, Kab. Pasuruan, Province. East Java. Gravel sand mining The sale value of natural products (sirtu) can be increased by processing and refining. The feed material is brought to the stone crusher and sand washing plant with the production of stone split 1 cm – 1 cm, 1 cm – 2 cm, 5 cm – 10 cm and sand wash with a silt content of less than 5%. In 1 cycle of pond maintenance, the feed material that can be processed is 1587.15 tons with a maintenance schedule every 6 days in all pond segments. Sludge impurities from the process washing sand flowed into pond one and experienced as much sedimentation 298.5 m 3 /6 days, pool two as much 313.98 m3 / 6 day, pool three as much 365.7 m3 / 6 day, and pool four as much 385.5 m3 / 6 day. Maintenance settling pond very need done because water in a settling pond reused for washing sand so that very influential on quality sand which in earn